2019
DOI: 10.1021/acs.jafc.9b02188
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Features of Hydrolyzable Tannins Determine Their Ability to Form Insoluble Complexes with Bovine Serum Albumin

Abstract: The ability of 32 purified and characterized hydrolyzable tannins to form insoluble complexes with model protein bovine serum albumin was investigated with a turbidimetric 96-well plate reader method. The results showed a clear relationship between the hydrolyzable tannin structure and the intensity of haze that formed during the tannin–protein complexation. In addition to molecular weight, structural features such as number of galloyl groups, degree of oxidative coupling between the galloyls, positional isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 46 publications
17
53
0
Order By: Relevance
“…This suggests that the substitution of anomeric position 1 of glucose has a much larger impact on the hydrophobicity than other positions. The importance of the anomeric position of glucose has also been witnessed in other HT structure-activity relationship studies before but mainly with the configuration of the anomeric hydroxyl group in C-glycosidic ellagitannins regarding their oxidative activity, protein precipitation capacity and how efficiently they effect the eff hatching and motility of Haemonchus contortus larvae [1,2,5]. When 1,2,3,4,6-penta-O-galloyl-β-d-glucose (19) is galloylated further into hexa- (26), hepta-(31) and octagalloylglucoses (32) forming digalloyl or even trigalloyl groups the hydrophobicity of the compounds decreases almost as drastically as it rises in the GG series.…”
Section: Galloylglucoses and Gallotanninsmentioning
confidence: 93%
See 1 more Smart Citation
“…This suggests that the substitution of anomeric position 1 of glucose has a much larger impact on the hydrophobicity than other positions. The importance of the anomeric position of glucose has also been witnessed in other HT structure-activity relationship studies before but mainly with the configuration of the anomeric hydroxyl group in C-glycosidic ellagitannins regarding their oxidative activity, protein precipitation capacity and how efficiently they effect the eff hatching and motility of Haemonchus contortus larvae [1,2,5]. When 1,2,3,4,6-penta-O-galloyl-β-d-glucose (19) is galloylated further into hexa- (26), hepta-(31) and octagalloylglucoses (32) forming digalloyl or even trigalloyl groups the hydrophobicity of the compounds decreases almost as drastically as it rises in the GG series.…”
Section: Galloylglucoses and Gallotanninsmentioning
confidence: 93%
“…Tannins are specialized plant metabolites, which are typically classified into three main subgroups based on their different structural features i.e., hydrolysable tannins (HTs), proanthocyanidins and phlorotannins. HTs have been shown to possess many nutritionally and pharmacologically beneficial activities such as oxidative activity, protein precipitation capacity and anthelmintic activity [1][2][3][4][5][6]. However, the hydrophobicities of these compounds have not been studied as much as the aforementioned activities even though it is likely one of the main factors when determining the mechanisms of their biological activity, lipid affinity and metabolism in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Only studies that reported results on individual compounds and tested the statistical significance of the studied relationship(s) were included. We estimated the oxidative and protein precipitation activities of the compounds using existing literature [38,39].…”
Section: Literature Surveymentioning
confidence: 99%
“…To evaluate the current evidence of the role of the studied polyphenols in plant defence against herbivores, we conducted a literature review on the relationship between herbivory and the individual polyphenol compounds measured in this study (see File C in S1 Appendix). We related the evidence gathered from the literature to two chemical characteristics of the compounds presumed to describe their anti-herbivore activity: oxidative activity and protein precipitation activity [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Purified ellagitannins with greater protein precipitation capacity tend to elute later during reversed-phase LC analyses due to their greater structural flexibility, lower water solubility and higher molecular mass Moilanen et al, 2013;Karonen et al, 2015;Engstr€ om et al, 2019). The following four structural features primarily increase the protein precipitation capacity and retention time of ellagitannins: the number of galloyl, HHDP and other functional groups attached to the central glucose core; the presence of two galloyls instead of one HHDP that is formed by C-C coupling of the two galloyls; the presence of a central glucopyranose unit instead of acyclic glucose; and the oligomerisation degree of the ellagitannin (Engstr€ om et al, 2019). Thus, separately integrating early-and late-eluting ellagitannins in complex mixtures of unidentified ellagitannins could provide useful information about the proportional biological activity of these compounds.…”
Section: Researchmentioning
confidence: 99%